Antimicrobial Usage Surveillance Through Sales at Veterinary Drug Shops Intended for Livestock in Vietnam - Ha, Le Thi Thu; Rueanghiran, Chalalai; Giang, Nguyen Thi Huong; Thuy, Doan Phuong; Phu, Doan Hoang; Tuan Kiet, Bach; Hien, Vo Be; Hue, Le Thi; Padungtod, Pawin; Truong, Bao Dinh; Carrique-Mas, Juan J. (Frontiers in Sustainable Food Systems, 2021)
There is a pressing need to establish surveillance systems for antimicrobial use (AMU) intended for animal production particularly in many low- and middle-income countries. In Vietnam, farmers commonly buy antimicrobials from veterinary drug shops (VDS). Therefore, VDS are a potential target for data collection on AMU. We collected antimicrobial sales data at VDS and estimated the amount of AMU in different animal species by antimicrobial active ingredient (AAI) class using different measurement metrics. We compiled information on all antimicrobials licensed in Vietnam and used this information to develop an application to capture sales of antimicrobials intended for use in poultry, pig, and ruminant. We provided tablets with this application to 60 VDS in two provinces (Bac Giang and Dong Thap; three districts and 30 VDS per province) for data collection over three weeks. Total sales of antimicrobials were extrapolated to one year, and these amounts were related to three different denominator estimates in each province including standing animal body weight, animal biomass, and Population Correction Unit (PCU). A total of 3,960 transactions of 831 different antimicrobial-containing products were recorded. Sales of 57 AAIs belonging to 17 classes were recorded. In the three Bac Giang districts, we estimated that 242.0kg of AAI were hypothetically sold over one year. Of those, 202.2kg (83.6 %) were intended for poultry, 19.8kg (8.1 %) for pigs, and 20.0kg (8.3 %) for ruminants. In Dong Thap, an estimated 48.4kg of antimicrobials were sold, including 28.9kg (59.7 %) for poultry, 16.0kg (33.1 %) for pigs, and 3.5kg (7.2 %) for ruminants. After standardized by different animal population denominators, AMU in Bac Giang amounted to 1,129.2 mg/kg standing animal body weight, 480.2 mg/kg biomass, and 636.1 mg/kg PCU. In Dong Thap, AMU figures were 1,211.0 mg/kg standing animal body weight, 595.8 mg/kg biomass and, and 818.5 mg/kg PCU. We discuss the observed differences between species, location and metrics, as well as the potential advantages and limitations of this methodology. Retail level data collection can effectively be integrated into AMU surveillance systems that help identify priority AMU management areas, establish national benchmarks and reduction targets.